Kediripedia Online Media Editor's Strategy For Increasing Generation Z's Reading Interest - Lukman Hakim; Yani Febriyanti; Siti Ayu Nur Fitriyah; Nonik Meieka (Fidikom UIN Jakarta, 2023)
Generation Z was born when digital technology was developing rapidly. They learned quickly and grew into a generation adept at using digital devices such as laptops, smartphones, tablets, and others. As a result, Generation Z spend more time using digital devices, exploring the virtual world, and interacting on social media than interacting face-to-face in real life. This behavior also arises because most of their daily activities are close to gadgets, so it becomes a new habit and impacts the decline in interest in reading. For this reason, means and ways are needed to change these habits. This research aims to find Kediripedia.com's strategy to generate interest in reading among Gen Z. The findings show that Kediripedia.com generate a strategy to increase young readers' interest in reading by taking two approaches. First, Kediripedia.com researched Gen Z to find out what kind of content and information presentation criteria interest them. Second, Kediripedia.com uses multi-platform information presentation by combining text, images, videos, and attractive visual design to create a playful yet accurate and credible information package for all groups, especially Generation Z.